Revista H2 - Santos, João Paulo Monteiro [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The objective of this project is to foment and promote the themes related to the Hip Hop movement through a product, the H2 Magazine. Based on several forms of journalism, like photos, reports and interviews, we intend to demonstrate the use of Hip Hop as a vindicatory tool for young people living in the outskirts of towns. Moreover, we seek showing distinct visions and develop the issues in a broad and comprehensive way. H2 is an open space for reflections about Hip Hop, a cultural movement present in Bauru, as well as your importance in the social and cultural development of the citizens

O objetivo deste projeto é fomentar e promover os temas ligados ao movimento Hip Hop por meio de um produto, a Revista H2. A partir de diversas formas de jornalismo, como fotos, reportagens e entrevistas, pretendemos demonstrar a utilização do movimento Hip Hop como ferramenta reivindicatória de jovens que vivem na periferia. Buscamos, ainda, mostrar visões distintas e desenvolver os assuntos de forma ampla e completa. H2 é um espaço aberto para reflexões sobre um movimento cultural bastante presente na cidade de Bauru, assim como sua importância no desenvolvimento social e cultural dos cidadãos
Keywords: Jornalismo eletrônico; Jornalismo cientifico; Mídia digital; Internet; Jornalismo e literatura; Online journalism